2015
DOI: 10.1075/sl.39.1.07pol
|View full text |Cite
|
Sign up to set email alerts
|

Why is there a Present-Day English absolute?

Abstract: International audienceWhereas the Present-day English (PDE) absolute construction has traditionally been labelled an infrequent, archaic and formal Latinism (Quirk et al. 1985: 1120), some recent studies have contested this view by claiming that the construction is still more productive than often thought (Kortmann 1991:2, König & van der Auwera 1990: 349). In addition, researchers have pointed out that cross-linguistically, English makes significantly more use of this construction than other Germanic language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Other types of subordinate adverbial clauses seem to have increased as well. Killie & Swan (2009) provide evidence that adverbial - ing clauses over time have become less appositive and more subordinate, while van de Pol & Petré (2015) show that adverbial uses of absolutes – among other increasing uses – are much more frequent in English from the late Early Modern English period onwards than they are in Dutch, which is arguably more like the earlier stages of English in this respect.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Other types of subordinate adverbial clauses seem to have increased as well. Killie & Swan (2009) provide evidence that adverbial - ing clauses over time have become less appositive and more subordinate, while van de Pol & Petré (2015) show that adverbial uses of absolutes – among other increasing uses – are much more frequent in English from the late Early Modern English period onwards than they are in Dutch, which is arguably more like the earlier stages of English in this respect.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…From a diachronic perspective, Killie & Swan (2009) argue that FAs were initially restricted to expressing relations of elaboration and accompanying circumstance, but came to prefer strongly adverbial uses. ACs, on the other hand, appear to have undergone the opposite development from more strongly adverbial to less informative elaboration uses (van de Pol 2014). In light of Kortmann's claims regarding the relation between syntactic and semantic linkage, these findings suggest that as the network of adverbial ing- clauses formed, these clauses came to be organized according to the iconicity principle, with subjectless ing -clauses expressing more informative relations, and constructions with overt subject being preferred for less informative uses.…”
Section: The Adverbial Ing-clause Network: Forms and Functionsmentioning
confidence: 99%
“…ACs, as shown in (17), were also steadily becoming more diverse, as they started taking objects and adverbial complements of their own much more often. In addition, they started being used in quasi-coordinate contexts (paraphrasable by an and -coordinated clause with finite verb form), as in example (18) (van de Pol 2014). As a result, the semantic features of the AC started to coincide with FAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to frequency, English absolute clauses are traditionally believed to be infrequent (Quirk et al, 1985(Quirk et al, , p. 1120, archaic, rather than stylistic (Higa, 2023), and should be avoided in writing (Sweet, 1903, p. 124). However, with the use of corpus-based quantitative approach and diachronic method, it was found that English absolute clauses are frequent in the genre of fiction and tend to be increasingly used in Present-Day English (He & Yang, 2015;Kim, 2020;van de Pol & Hoffmann, 2016;van de Pol & Petré, 2015). Despite the useful findings, the reasons for their appearances in a specific context such as fiction have not yet been explored.…”
mentioning
confidence: 99%